2006
DOI: 10.1097/01.wnp.0000229045.28725.5c
|View full text |Cite
|
Sign up to set email alerts
|

Abruptly Attenuated Terminal Ictal Pattern in Pediatrics

Abstract: The minority of pediatric seizures recorded in a tertiary epilepsy monitoring unit end with diffuse, synchronized abrupt attenuation. AAT probably is the result of an active process that is developmentally related. It appears to require some degree of mature and intact neurophysiology and may involve the thalamocortical circuit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 8 publications
1
15
1
Order By: Relevance
“…PGES occurs in between 8% of pediatric seizure patients (Kim et al 2006) to 65% or more of adult patients with GTCS (Lhatoo et al 2010) and has been reported in several monitored SUDEP/near SUDEP cases (Bateman et al 2010, Bird 1997, Lhatoo et al 2010, McLean & Wimalaratna 2007, So et al 2000, Tao et al 2010) where some authors have used the term “cerebral shutdown” (McLean & Wimalaratna 2007). The increased incidence and duration of PGES in adults is noteworthy as they are a higher risk population than children.…”
Section: Discussionmentioning
confidence: 99%
“…PGES occurs in between 8% of pediatric seizure patients (Kim et al 2006) to 65% or more of adult patients with GTCS (Lhatoo et al 2010) and has been reported in several monitored SUDEP/near SUDEP cases (Bateman et al 2010, Bird 1997, Lhatoo et al 2010, McLean & Wimalaratna 2007, So et al 2000, Tao et al 2010) where some authors have used the term “cerebral shutdown” (McLean & Wimalaratna 2007). The increased incidence and duration of PGES in adults is noteworthy as they are a higher risk population than children.…”
Section: Discussionmentioning
confidence: 99%
“…The exact cause of the discrepancy is unclear, but children tend to have a lower prevalence of PGES (Kim et al, 2006;Semmelroch et al, 2012;Pavlova et al, 2013), shorter PGES durations, shorter tonic duration during their GTCS (Freitas et al, 2013), and a higher level of supervision at night (Thurman et al, 2014).…”
Section: Post-ictal Autonomic Changes In Adults Versus Pediatric Patimentioning
confidence: 94%
“…The report by Verma et al [3] studied 13 patients with bilateral depth arrays and examined the side of termination in the context of outcome. A recent study of scalp patterns in children discusses an abruptly attenuated terminal ictal pattern which is synchronous termination, but this was more common in idiopathic and generalized seizures, a different population than has been studied elsewhere [7]. …”
Section: Introductionmentioning
confidence: 99%